Cyber Security: A Growing Challenge to Pakistan - Shabbir, Nida; Adnan, Mubeen (Annals of Human and Social Sciences, 2025)
Pakistan's dependence on digital infrastructure and quick adoption of new technologies have made cybersecurity issues worse. Information security breaches, cyber assaults, identity theft, a state-run digital warfare, and spying are just a few of the many challenges the nation confronts. These dangers jeopardise the commercial, industrial, and financial sectors in addition to compromising vital government and defense data. Pakistan's weaknesses are caused by things like a lack of technological know-how, antiquated regulations, and ignorance on the part of both individuals and companies. Investigating these cybersecurity concerns, their effects on national security and financial stability, and the steps that must be taken to resolve them are the objectives of this article. Utilising a qualitative technique with a phenomenological perspective, the study uses secondary sources and an exploratory and descriptive design. In order to improve cybersecurity, it highlights the pressing need for strict laws, cutting-edge technology, and international cooperation. Addressing cybersecurity issues is essential in the current digital era for societal adaptability, economic prosperity, and national security in addition to technological advancement.